SUBSURFACE RESISTIVITY DISTRIBUTION MODELLING IN GEOELECTRICAL SURVEY USING FINITE DIFFERENCE METHOD - NUR AINI (NIM: 20214054), DIAN
Subsurface resistivity distribution modelling using finite difference method have been carried out. As a comparison, author used an analytical equation of Bessel function integral and image method from Laplace differential equation for multilayer earth model. That equations are obtained by applying boundary condition. First, current flux is equal to zero at the earth surface. Second, current flux and electrical potential is continous at the two layer boundary. So that, a resistivity equation for n multilayer earth model is found. Furthermore, the resistivity equation is used for numerical programming with two methods which are Finite Difference and analytical method to get electrical potential curve. The last, models of earth subsurface by both Finite Difference and analytical methods are compared by calculating electrical potential. So the conclusion is image method has higher accuration than Bessel integral function method for two layer earth model. Keywords: Forward Modelling, Image Method, Finite Difference Method, Bessel Function Integral, Resistivity.